Genetic-gonadal-genitals sex (3G-sex) and the misconception of brain and gender, or, why 3G-males and 3G-females have intersex brain and intersex gender - Joel, Daphna (BioMed Central, 2012)
The categorization of individuals as “male” or “female” is based on chromosome complement and gonadal and genital phenotype. This combined genetic-gonadal-genitals sex, here referred to as 3G-sex, is internally consistent in ~99% of humans (i.e., one has either the “female” form at all levels, or the “male” form at all levels). About 1% of the human population is identified as “intersex” because of either having an intermediate form at one or more levels, or having the “male” form at some levels and the “female” form at other levels. These two types of “intersex” reflect the facts, respectively, that the different levels of 3G-sex are not completely dimorphic nor perfectly consistent. Using 3G-sex as a model to understand sex differences in other domains (e.g., brain, behavior) leads to the erroneous assumption that sex differences in these other domains are also highly dimorphic and highly consistent. But parallel lines of research have led to the conclusion that sex differences in the brain and in behavior, cognition, personality, and other gender characteristics are for the most part not dimorphic and not internally consistent (i.e., having one brain/gender characteristic with the “male” form is not a reliable predictor for the form of other brain/gender characteristics). Therefore although only ~1% percent of humans are 3G-“intersex”, when it comes to brain and gender, we all have an intersex gender (i.e., an array of masculine and feminine traits) and an intersex brain (a mosaic of “male” and “female” brain characteristics).